(untitled) (Eurasian Journal of Learning and Academic Teaching, 2021)
The issue that we consider in this paper - the role of home reading in foreign language teaching and the organization of foreign language lessons - is one of the most important up-to-date problems. I would like to make a reservation at once, the concept home reading - a reading of the work in a foreign language in the original. It seems to us only the language of art works by matching usually standards of modern literary language is not replaceable as a model for the study of a foreign language, and the role that the sample is especially great, as is taught as secondary linguistic community.